2014
DOI: 10.1111/dmcn.12570
|View full text |Cite
|
Sign up to set email alerts
|

Association between motor functioning and leisure participation of children with physical disability: an integrative review

Abstract: Aim The aim of this integrative review is to synthesize the evidence of association between motor functioning and leisure participation of children with physical disability. Method We conducted a systematic electronic search of key databases from the period 1 January 2001 to 30 April 2014 using relevant keywords. The Mixed Method Appraisal Tool was used to assess the quality of the qualitative and quantitative studies included and carried out in children with physical disability aged 6 to 12 years. We synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…[96][97][98][99] The conceptual framework developed through an integrative review by Kanagasabai et al 100 suggests contextual conditions under which participation is reduced or maintained ( Figure 2). Another review, by Kang et al, 101 proposes that participation is optimised with physical, social and self-engagement.…”
Section: Modelling Process: Developing Programme Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…[96][97][98][99] The conceptual framework developed through an integrative review by Kanagasabai et al 100 suggests contextual conditions under which participation is reduced or maintained ( Figure 2). Another review, by Kang et al, 101 proposes that participation is optimised with physical, social and self-engagement.…”
Section: Modelling Process: Developing Programme Theorymentioning
confidence: 99%
“…Predictably, 100,191 some parents reported that their boys were increasingly frustrated at the loss of function (see Perceived improvement in confidence, independence or participation) and consequent withdrawal from sport, play (d880) and their peer group (d7500).…”
Section: Participation Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key areas for assessment include home, school and community settings (8)(9)(10)(11). A complex interaction of personal characteristics, skills, and motivation (9,11,12) as well as environmental factors (10,13) influence participation. Recent developments (1) focus on a biopsychosocial conceptualization of child functioning, in particular not focusing solely on conditions (body functions and body structures), but instead aiming to assess and understand activities and participation in context (1).…”
Section: Introductionmentioning
confidence: 99%
“…Children with CP participate in leisure-time physical activities (PA) less often, 9 with less intensity 10 and with reduced diversity than their typically developing peers. 11 Children and youth with CP and physical disabilities also participate in more informal compared with formal (organised and structured) PA. 11 12 A longitudinal study in young children with CP aged 2–6 years found that activity limitations could predict reduced participation in leisure-time PA. 13 An integrative review of the relationship between motor functioning and leisure participation for young children with a physical disability also concluded that suboptimal motor functioning impacts frequency and diversity of participation in PA. 14 Children with physical disabilities, however, preferred to participate in PA over other types of activity irrespective of their level of motor functioning. 14 This evidence suggests that in the presence of support that enables participation in the activity of choice, the individual preferences of a child and other psychosocial aspects may be equally important determinants to the extent of participation.…”
Section: Introductionmentioning
confidence: 99%